Life Skills Children Aged 4-6 Years in Sragen - Hasanah, Fathimah; Pranoto, Yuli Kurniawati Sugiyo Pranoto; Diana, Diana (JURNAL PENDIDIKAN USIA DINI, 2024)
The abilities of children aged 4-6 years in Sragen Regency look poor, it is thought that this is because life skills at school and at home are not instilled well and in harmony. The aim of this research is to analyze how the life skills of children aged 4-5 years in Sragen district are seen from the age, gender and type of work of the parents. This research uses mixed methods, namely quantitative and qualitative. The results of the findings explain that children's life skills The age of 6 years looks better and because of the adjustments the cultivation of life skills is carried out at home and at school. The life skills possessed by children aged 4 years seem to be starting to emerge in the aspects of personal skills (including self-knowledge skills, rational thinking skills) and social skills (including functional language skills, empathy skills). The life skills of children aged 5 years seem to have developed in those who are female and are supported by the type of work and educational background of their parents in the form of Strata 1. Likewise, the life skills of children aged 6 years in female children have more life skills that are very developed from of personal skills and social skills.Several factors influence the development of life skills. What teachers do at school is as follows: starting from giving examples at school, giving invitations and commands and doing it directly to the children. This is the instillation carried out by teachers at school so that children receive life skills stimulus in the form of personal skills and social skills which become the basic provisions for life for children aged 4-6 years which are also supported by stimuli which are followed up at home by parents.